Perencanaan Instalasi Pengolahan Air Minum di Kecamatan Cisarua, Kabupaten Bandung Barat - Aditya Rifqi Rizqullah; Mohammad Rangga Sururi; Etih Hartati (Jurnal Serambi Engineering, 2024)
The Cisarua Subdistrict is part of West Bandung Regency with a population of 80,298 people in the year 2022 and an area of 55.63 km2. The development of West Bandung Regency is related to the increasing demand for drinking water. The Regional Water Company (PDAM) is needed to meet the supply of water and ensure its quality is safe. The planning of the Drinking Water Treatment Plant (IPAM) is aimed at planning the water needs in Cisarua Subdistrict, West Bandung Regency to be sufficient for the next 20 years. To plan the IPAM, it is necessary to carry out population projections, water demand projections, water quality analysis and unit selection. The projected population in the year 2042 using the arithmetic method is 105,628 people, and the projected total water demand is 210 L/second. In the results of this planning, the treatment units used are intake, coagulation, flocculation, sedimentation, and disinfection.